Evaluation of Isolated Compounds Activity from Convolvulus Arvensis Against Algae - Shoker, Roaa; Jawad, Abdul-Latif (Iraqi Journal of Science, 2023)
This study includes isolation, purification, and identification of algae from different aquatic environments in Baghdad city. Nine unialgal cultures were obtained. These algal cultures included 6 species of blue-green algae (Microcystis aeruginosa, Microcystis flos-aquae, Oscillatoria limnetica, Nostoc carneum, Westillopesis prolifica, Mastigocluds lamiosus), and 3 species of green algae (Mougeotia sclaris, Scenedesmus dimorphus and Chlorella vulgaris). In addition that aerial parts from Convolvulus arvensis were collected. Terpens, alkaloids and phenols were extracted of mentioned plant, and the antialgal activity of extracts types were evaluated in 3 concentrations (5, 10, and 20 mg/ml) by wells and diffused in the agar media. Results showed that phenols extracts from C. arvensis were the most effective against isolated algae than other extracts, and terpens extracts were less effective. O. limentica was the most sensitive to attack by extracts than other algae, while N. carneum was lower sensitive, also W. prolifica, M. lamiosus were the most resistance to attack by C. arvensis extracts.Chemical composition of phenols and alkaloids were analyzed by High Performance Liquid Chromatography (HPLC) and showed that present 10 phenolic compounds, 8 alkaloid compounds in C. arvensis.